A STUDY ABOUT MASTITIS INFECTION CHARACTERISTICS IN DAIRY COW OF BAVI, HANOI, VIETNAM - Van Thanh, Nguyen; Thanh Hai, Nguyen; Ngoc Son, Nguyen; Van Dung, Bui; Atsushi, Miyamoto (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The present research was performed to investigate the prevalence of mastitis infection in Bavi, Hanoi, Vietnam and also to study the relationship between places, seasons and cow breeds with the disease occurrence. Methods: Mastitis infection was diagnosed by clinical symptoms observation and California Mastitis Test (CMT). The results of these 2 methods were then analyzed to understand the clinical and subclinical infection. The infected cases were also separated to different places and breeds to analyze the relationship with disease prevalence. In the seasonal investigation, the mastitis infection was diagnosed continuously over one year with the aid of farm managers and local veterinarians.Â  Results: Positive infection detected by CMT kits were significantly higher than that of the clinical symptoms diagnose, suggested the involvement of subclinical infection cases, the infection in which no clinical symptoms could be observed. There was no significance difference between places and seasons, however the occurrence in summer was higher than other seasons. The Holstein Friesian (HF) purebred had significantly higher infection rates compare to crossbreds. In addition, there is a trend of increased percentage of the prevalence of mastitis in higher generations. Conclusion: The prevalence of mastitis in Bavi is lower than other parts of Hanoi and other places in Vietnam. Crossbreds F1HF and F2HF had significantly low sensitivity to mastitis and were recommended for dairy cow husbandry. Summer is the most risky time for mastitis and therefore requires the application of appropriate preventive methods. Key words: clinical mastitis, subclinical mastitis, dairy cows, breed, season, prevalence, Bavi